Pengaruh Konseling terhadap Kepatuhan Suplementasi Tablet Besi (Fe) pada Ibu Hamil di Kabupaten Lumajang - Antonius Nugraha Widhi Pratama; Nanda Puspasari; Fransiska Maria Christianty (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
The prevalence of iron deficiency anemia in Indonesia is relatively high. However, adherence to iron supplementation among pregnant women is relatively low, even though the supplementation is provided free of charge by the government. Counseling is expected to increase patient adherence. Therefore, the present research was to study the effect of counseling on adherence to iron supplementation among pregnant women. A number of 62 respondents from a primary health center in Lumajang Regency were recruited after they gave informed consent and equally allocated to control and treatment groups based on their area residence. The control group received routine antenatal service, while the treatment group received the additional counseling using a brochure. The average of adherence score, based on Morisky Medication Adherence Scale-8 (MMAS-8), in the treatment group (5.9±1.9) was significantly different (p=0.027) from the control group (5.0±1.2). Counseling with brochure appeared to be effective to improve adherence to iron supplementation for pregnant women. Keywords: adherence, iron suplementation, pregnancy, pharmacy counseling